Pengaruh Financial Literacy dan Risk Tolerance Terhadap Keputusan Nasabah Dalam Pemilihan Instrumen Investasi Tabungan Emas di PT Pegadaian (Persero) Cabang Jombang - Lailatul Maghfiroh (JFAS : Journal of Finance and Accounting Studies, 2020)
Financial literacy is a series of processes or activities to increase the knowledge of an individual so that they are able to manage personal finances for the better future. While risk tolerance is an ability that can be accepted by investors in taking an investment risk. This research is to know: (1) the influence of financial literacy on the saving of investment of customer of gold saving. (2) the influence of risk tolerance on the investment savings of gold saving customers.The population in this study are customers who are registered as active customers in PT Pegadaian (Persero) Jombang Branch. This research uses causal associative method with multiple regression analysis model. The results of this study indicate that: (1) Financial literacy has a positive influence on investment decision of gold saving customers. (2) Risk tolerance has a positive influence on the investment decision of gold saving customers. This research uses causal associative method with multiple regression analysis model.